2023
DOI: 10.1186/s12883-023-03242-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between key continuous glucose monitoring-derived metrics and specific cognitive domains in patients with type 2 diabetes mellitus

Abstract: Background Continuous glucose monitoring (CGM)-derived time in range (TIR) is closely associated with micro- and macrovascular complications in type 2 diabetes mellitus (T2DM). This study was performed to investigate the relationship between key CGM-derived metrics and specific cognitive domains in patients with T2DM. Methods Outpatients with T2DM who were otherwise healthy were recruited for this study. A battery of neuropsychological tests was pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Our results revealed a significant association between hyperglycaemia metrics (including a higher mean SG and TAR) and cognitive function changes. These findings supported the observations of previous studies 9,11,13 . Our longitudinal study design further strengthened these results as the temporal association was examined.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results revealed a significant association between hyperglycaemia metrics (including a higher mean SG and TAR) and cognitive function changes. These findings supported the observations of previous studies 9,11,13 . Our longitudinal study design further strengthened these results as the temporal association was examined.…”
Section: Discussionsupporting
confidence: 91%
“…A recent cross‐sectional study showed that a higher TBR was significantly associated with worse cognitive performance, particularly with memory, visuospatial ability and executive function among 96 outpatients with mean age of 61 years. However, TIR or glycaemic variability was not associated with any cognitive function 11 . This discrepancy in the results may be because of differences in the target population, particularly regarding the presence of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations